2016
DOI: 10.5688/ajpe80348
|View full text |Cite
|
Sign up to set email alerts
|

A Scenario-Based Virtual Patient Program to Support Substance Misuse Education

Abstract: Objective. To evaluate virtual patient (VP) programs for injecting equipment provision (IEP) and opiate substitution therapy (OST) services with respect to confidence and knowledge among preregistration pharmacist trainees. Methods. Preregistration trainee pharmacists pilot-tested the VP programs and were invited to complete pre/post and 6-month assessments of knowledge and perceived confidence. Results. One hundred six trainees participated and completed the pre/postassessments. Forty-six (43.4%) participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…Eight (14.3%) studies involved pharmacists [10][11][12][13][14][15][16][17], one (1.8%) involved pre-registration pharmacists [18], forty-six (82.1%) involved pharmacy undergraduate students and one (1.8%) involved both pharmacists and pharmacy students [9]. The number of participants ranged from eight in the smallest study [34], up to seven hundred and ninety-two in the largest [13].…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight (14.3%) studies involved pharmacists [10][11][12][13][14][15][16][17], one (1.8%) involved pre-registration pharmacists [18], forty-six (82.1%) involved pharmacy undergraduate students and one (1.8%) involved both pharmacists and pharmacy students [9]. The number of participants ranged from eight in the smallest study [34], up to seven hundred and ninety-two in the largest [13].…”
Section: Participantsmentioning
confidence: 99%
“…Learning was also assessed subjectively, through pre-, mid-and post-intervention surveys in twenty-six (46.4%) studies [11,12,[14][15][16][17][18][19]23,25,29,30,35,37,[41][42][43]45,46,50,52,56,57,59,62,64] and all but two [19,42] of these studies reported that the e-learning intervention was effective. Taglieri et al, [19] investigated the effect of completion of online virtual patient cases on student performance and confidence in mock clinic visits.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, the majority of VP cases have not focused on SDM, focusing either on the technical aspects of care 10 or patient-centred counselling. 11 In real practice clinicians are required to do both; it is not acceptable to be kind and caring but clinically incompetent and vice versa. We therefore designed a VP that allows the user to practice SDM, drawing on their technical skills as well as their ability to have a patient-centred conversation.…”
Section: Introductionmentioning
confidence: 99%